Development and evaluation of a self-generated foam–resin composite sand consolidation system for offshore oil reservoirs - Mengsheng Jiang; Shanfa Tang (PLoS ONE, 2025)
Sand production poses a major challenge in offshore heavy oil development, leading to casing erosion, equipment damage, and wellbore instability, which ultimately results in production decline. Conventional mechanical and chemical sand control methods often exhibit limited effectiveness in fine-grained or high-salinity formations and may induce formation damage or high operational costs. This study developed a self-generated foam–resin composite sand consolidation system to address these issues. The system integrated a controllable gas-generating subsystem and a melamine–formaldehyde (MF) resin matrix, thus enabling in-situ foam generation and sand consolidation. Laboratory experiments were conducted in three stages: optimization of gas and foaming agent subsystems, formulation and evaluation of the resin-based consolidant, and integration testing of the composite system. The optimized formulation resulted in controllable gas production, high foam stability, and consolidated sand cores with compressive strength >7 MPa. The system exhibited thermal stability up to 90 °C, salinity resistance, moderate permeability (~4 μm 2 ), non-adhesion to metal surfaces, and negligible sand production (<0.1%) under dynamic water flooding. These results indicate that the foam–resin composite system provides an efficient, environmentally compatible, and cost-effective solution for sand control in complex offshore heavy oil reservoirs.